EQUILIBRIUM CONDITION FOR NANO-SIZE TWINS EMBRYO - O. M. Ostrikov (Наука и техника)
The paper proposes a dislocation model of nano-twins. On the basis of equilibrium condition an analysis of forces resisting to the process of twins embryo development has been done in the paper.